Acetalization of 5-hydroxymethyl furfural into biofuel additive cyclic acetal using protic ionic liquid catalyst- A thermodynamic and kinetic analysis. (April 2021) - Kumar, Komal; Pathak, Shailesh; Upadhyayula, Sreedevi
Abstract: This work investigates the thermodynamics and kinetics of the synthesis of 5-HMF-cyclic acetal, a fuel additive, from 5-HMF and 1, 3-propanediol using lab synthesized, environmentally benign Brønsted acidic ionic liquid (IL) catalyst. Firstly, a thermodynamic study of the acetalization of 5-HMF with different mono and polyalcohols was carried out to evaluate the thermodynamic properties of critical temperature ( T c ), critical volume ( V c ), critical pressure ( P c ), Gibbs free energy of formation ( Δ G f 0 ), enthalpy of formation ( Δ f H 0 ), and heat capacity ( C p ) using group contribution methods. Then, kinetics of 5-HMF acetalization with 1, 3-propanediol was investigated in a batch autoclave using Brønsted acidic IL catalyst and effect of reaction parameters temperature, molar ratio of reactants and time were investigated on the conversion of 5-HMF into 5-HMF-cyclic acetal product and optimized for high 5-HMF conversion and cyclic acetal yield. A first-order pseudo-homogeneous kinetic model with a squared regression coefficient R 2 > 0.99 fitted well with experimental data. The activation energy of the acetalization reaction is estimated to be 83 kJ/mol for the 1 st order kinetics. Based on the catalyst activity, a plausible reaction mechanism was proposed for the acetalization reaction of 5-HMF and 1, 3-propanediol. Finally, this manuscript reports an efficient method for the production of fuel-additive compound and valuable information for predicting the thermodynamic properties for the pure organic components. Graphical abstract: Image 1 Highlights: Thermodynamics, Kinetics of [IL-SO3 H][CF3 SO3 ] catalyzed 5-HMF acetalization with 1, 3-propanediol. 99.2% 5-HMF conversion at 313 K at 150min. Pseudo-first order kinetics best fit the reaction data. Activation energy is 83 kJ/mol in 293–343 K range. Δ G f 0, Δ f H 0, C p, critical PVT determined by group contribution methods.